A Systematic Review of Lemierre’s Syndrome With a Focus on Ophthalmologic Complications - Dasari, Suhas P (Cureus, 2020)
Lemierre’s syndrome (LS), once known as “the forgotten disease,” is a rare and potentially life-threatening condition that has had a gain in incidence over the last 30 years due to a variety of factors that could include changes in antibody prescription patterns, particularly in regard to the treatment of pharyngitis/tonsillitis. Due to its low incidence and broad spectrum of symptoms, LS does not have an obvious clinical diagnosis and can confuse the clinician managing the patient. Furthermore, it is equally difficult to treat patients suffering from LS as it requires a multidisciplinary approach from multiple subspecialties. Thus, communication between hospitalists, radiologists, otolaryngologists, neurologists, and ophthalmologists is critical towards quickly diagnosing the disease condition so that prompt antibiotics, anticoagulation, and surgical intervention can occur. Atypical presentations can also exist, making the diagnosis and management exponentially more challenging. Ophthalmologic symptoms are a particularly rare and atypical presentation of LS. These rare symptoms in LS can be terrifying for patients and providers alike; yet, there does not seem to be any modern medical literature that summarizes ophthalmologic complications for LS patients. To our knowledge, this is the first systematic review of LS with a focus on ophthalmologic complications that has been done. The main objective of this review paper is to provide an up-to-date literature review of LS epidemiology, pathophysiology, diagnosis, and treatment while also performing a novel systematic review of reported cases of LS with ophthalmological complications. We hope to bring more awareness towards LS and its atypical presentations so that physicians will be better able to rapidly diagnose and treat their patients in order to minimize long-term morbidity and mortality.